2020
DOI: 10.5415/apallergy.2020.10.e37
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of Good syndrome: acute hepatitis from hepatitis B virus reactivation

Abstract: Good syndrome (GS) is a primary immunodeficiency (PID) that presents in middle aged to older adults with features of thymoma, hypogammaglobulinemia, CD4 T lymphopenia, inverted CD4/CD8+ ratio, and impaired T-cell mitogen proliferative responses. We present a patient, a 62-year-old female, who first presented with disease manifestation of acute hepatitis from hepatitis B virus (HBV) reactivation, which was subsequently complicated by recurrent hospitalizations for recurrent pneumonia and concomitant Helicobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In these two cases the loss of protective anti-HBs antibodies due to hypogammablobulinemia is probably the trigger of HBV recurrence. Interestingly, a case of HBV reactivation in a patient with hypogammaglobulinemia in the context of Good syndrome has recently been described and may support our hypothesis (5). In our first patient, hypogammaglobulinemia is chronic and affects all Ig subclasses.…”
Section: Discussionsupporting
confidence: 83%
“…In these two cases the loss of protective anti-HBs antibodies due to hypogammablobulinemia is probably the trigger of HBV recurrence. Interestingly, a case of HBV reactivation in a patient with hypogammaglobulinemia in the context of Good syndrome has recently been described and may support our hypothesis (5). In our first patient, hypogammaglobulinemia is chronic and affects all Ig subclasses.…”
Section: Discussionsupporting
confidence: 83%
“…Lymphopenia may be a characteristic of patients with severe pneumonia infected with respiratory pathogens, including influenza viruses, coronaviruses, measles virus, and MP [88][89][90][91]. The severity of lymphopenia correlates with target cell injury in these diseases and chronic viral infections, including AIDS and hepatitis virus infections, when relapsed patients are severely affected [92,93]. Earlier experimental animal studies on respiratory pathogens, including influenza viruses and MP, have reported that extensive infiltration of small lymphocytes is observed in early lung lesions within 2-3 days after inoculation, before the appearance of virus-specific antibodies, irrespective of inoculation sites, such as intraperitoneal, oral, or intranasal routes [1].…”
Section: Protein Homeostasis (Proteostasis) Proteasome and Lymphopeni...mentioning
confidence: 99%